Multicentre study on inflammatory skin diseases from The International Confocal Working Group: specific confocal microscopy features and an algorithmic method of diagnosis. (18th April 2016) - Ardigo, M.; Longo, C.; Gonzalez, S.; ,
Summary: Background: The real value of reflectance confocal microscopy (RCM) for the evaluation of inflammatory skin conditions remains unclear. A project on RCM for inflammatory skin diseases involving international centres was designed by a coordinating centre and executed under the supervision of the International Confocal Working Group. Objectives: To identify specific confocal features useful for distinction between the three main groups of superficial inflammatory skin diseases. Methods: Nineteen different RCM features were evaluated in a total of 155 lesions, diagnosed as spongiotic (45), interface (52) or psoriasiform (58) dermatitis, collected by a consortium of 19 different centres. Results: Univariate and multivariate analysis identified RCM descriptors for the three main superficial inflammatory disease groups. Later, a multivariate method was employed to define a scoring system to be applied on an algorithmic method of analysis for fast clinical application. Conclusions: Our preliminary evaluation supports the use of RCM for the identification of confocal patterns consistent with the major features of the diagnostic groups of inflammatory skin diseases. Moreover, an efficient multivariate method for clinical in vivo RCM diagnosis using a tree decision diagram has been established. Abstract : What's already known about this topic? Reflectance confocal microscopy has been used successfully for the evaluation of several inflammatory skin diseases. What does this study add? Reflectance confocal microscopy provides features useful for diagnosis and differential diagnosis of the major inflammatory skin diseases. An algorithmic method originating from multivariate analysis can be used for the diagnosis.